Analysis of Indonesian Charcoal Briquette Company Strategies for Improving Export Performance (Case Study on Charcoal Briquette Company, CV. Mega Briquette Semarang) - Putvika Indrasari; Amie Kusumawardhani (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This research aims to develop a qualitative research model by identifying the strategy of the CV. Mega Briquette company is facing obstacles in shipping charcoal briquettes and identifying the contribution of network capabilities and information capabilities to improving the company’s export performance. This research uses qualitative methods by conducting in-depth interviews with representatives from CV. Mega Briquette. The findings in this research are that networking capabilities and information capabilities are proven to contribute to improving export performance at CV. Mega Briquette. It is hoped that future research will be able to obtain more sources. It is hoped that future research will be able to obtain more sources so that it can explain the strategies used by other Charcoal Briquette companies to improve their companies’ export performance. Managerial Implications for Charcoal Briquette Companies in Improving Company Export Performance. This study explains the contribution of Network Capability and Informational Capability to export performance in a company. This research model is used to determine the contribution of network and informational capabilities in improving export performance in companies.